Effectiveness of Arbidol for COVID-19 Prevention in Health Professionals - Yang, Chunguang; Ke, Chunjin; Yue, Daoyuan; Li, Wengang; Hu, Zhiquan; Liu, Wei; Hu, Shuhua; Wang, Shaogang; Liu, Jihong (Frontiers in Public Health, 2020)
Background Frontline health professionals are a COVID-19-susceptible population during the outbreak of COVID-19, but prophylactic drugs against SARS-CoV-2 infection are to be explored. Method Frontline health professionals diagnosed with COVID-19 before February 9, 2020 in Tongji Hospital, Wuhan, China and the same amount of controls in the uninfected group were included in this study. Clinical and laboratory data were collected with standardised forms. Results A total of 164 subjects were included in this study, 82 cases in the infected group and 82 controls in the uninfected group, with a median age of 37 years, including 63 males and 101 females. Nineteen (23.2%) patients in the infected group were administered oral arbidol, and 48 (58.5%) in the uninfected group (OR = 0.214, 95% CI 0.109‒0.420). Forty-eight patients (58.5%) in the infection group were hospitalized, with a median age of 39 (31-49) years, of whom 7 (14.6%) were prophylactically administered arbidol. Thirty-four patients (41.5%) with mild symptoms were treated outside the hospital, among which the median age was 34 (30-39) years, and twelve patients (35.3%) took prophylactic oral arbidol. The hospitalization rate was significantly associated with age (P = 0.024) and oral arbidol administration (OR = 0.313, 95% CI 0.108- 0.909). In the age-matched case-control study, the hospitalization rate was not significantly associated with arbidol administration (P = 0.091). Conclusion Prophylactic oral arbidol is protective against SARS-CoV-2 infection but not hospitalization rate in health professionals, providing a basis for the selection of prophylactic drugs for high-risk populations.